Inter- and Intramolecular Dienamine Organocatalytic Strategies for the Synthesis of Tetrahydroisoquinolines and Tricyclic Derivatives via [3+2] and [4+2] Cycloadditions - Fraile, Alberto; Alemán, José (Synlett, 2015)
The use of dienamines represents a new approach for carrying out asymmetric aminocatalytic reactions controlled by a remote chiral catalyst. In this account, we describe our contributions on the use of dienamine methodologies for the synthesis of interesting compounds from a natural product and pharmaceutical point-of-view. Dienamine aminocatalysis is employed for the synthesis of tetrahydroisoquinoline derivatives via intermolecular [3+2] cycloadditions, and for the preparation of tricyclic products by means of intramolecular [4+2] Diels–Alder reactions.1 Introduction2 Intermolecular Dienamine versus Iminium Ion Catalysis: Synthesis of Tetrahydroisoquinoline Derivatives3 Intramolecular Dienamine Catalysis: Synthesis of Tricyclic Derivatives4 Outlook
Keywords: organocatalysis; dienamines; iminium ions; tetrahydroisoquinolines; tricyclic derivatives